KONSEP SINYAL INFORMASI PADA STASIUN PENGOLAHAN LIMBAH CAIR PLTBg POME - Stieven N. Rumokoy; Dezetty Monika; Langlang Gumilar (Universitas Raharja, 2019)
Biogas Electrical Power Plant require a good operational system. Good operational system could be mean there is a clear information about the condition from field. To make easier to get information from field, a concept of signal reader which picturing actual condition can be build. In Biogas Electrical Power Plant from POME (Palm Oil Mill Effluent), there is a Waste Water Treatment Station. The Operation of Waste Water Treatment Station should be well and safe operated, to reducing hazardous content of the waste water and get Biogas as a side product. On that operation, every equipment in that field need the right information for control purpose. The require signal analysis in waste water treatment station to get information actual condition from field to the main control has been done. It needs some signal such as Actif-unactif Status Indicator, Level Indicator, Flow Meter Indicator, Temperature Indicator, Pressure Indicator for Liquid and Pressure Indicator for Gas, respectively. This kind of signal as an information from field (Waste Water Treatment Station) to make operation easier and safe.